A few remarks on hybridity in Polish administrative law on the example of legal forms of action - Paulina Bieś-Srokosz; Jacek Srokosz (Wrocławsko-Lwowskie Zeszyty Prawnicze)
A hybrid in the broader culture may be associated with something heterogeneous, deviating from the usual standards, which may bring about anxiety and be an example of an anomaly. In ancient times, a hybrid was defined as a creature composed of at least two different elements, such as an ox with a human head. Despite all these years, hybridity has not changed. Of course, we refer to it in other aspects than just living beings, i.e. in arts, movies, and cars, but also to the legal instruments functioning in the current state of the law. In this article, it is the intention of the author to present the hybrid legal forms used by the public administration. However, the author’s approach to this subject was more theoretical than dogmatic, hence the considerations were focused on the creation or the purposefulness of functioning of these forms in administrative law.